Reconstructing the corporation : from shareholder primacy to shared governance / Grant M. Hayden, Matthew T. Bodie, Saint Louis University School of Law. - Hayden, Grant M.; Bodie, Matthew T. (Cambridge University Press, 2020)
Modern corporations contribute to a wide range of contemporary problems, including income inequality, global warming, and the influence of money in politics. Their relentless pursuit of profits, though, is the natural outcome of the doctrine of shareholder primacy. As the consensus around this doctrine crumbles, it has become increasingly clear that the prerogatives of corporate governance have been improperly limited to shareholders. It is time to examine shareholder primacy and its attendant governance features anew, and reorient the literature around the basic purpose of corporations. This book critically examines the current state of corporate governance law and provides decisive rebuttals to longstanding arguments for the exclusive shareholder franchise. Reconstructing the Corporation presents a new model of corporate governance - one that builds on the theory of the firm as well as a novel theory of democratic participation - to support the extension of the corporate franchise to employees.